Caregiver Choice and Caregiver Outcomes: A Longitudinal Study of Irish Spousal Dementia Caregivers - Pertl, Maria M.; Sooknarine-Rajpatty, Aditi; Brennan, Sabina; Robertson, Ian H.; Lawlor, Brain A. (Frontiers in Psychology, 2019)
Background The perception of choice in becoming a caregiver may impact on caregiver psychological and physical health. We determined the proportion of spousal dementia caregivers who felt they had a choice, and examined whether lack of choice in taking up the caregiving role and the perceived degree of choice in caregiving predicted caregiver health and wellbeing and care-recipient placement in long-term care at one-year follow-up. Methods We performed secondary analyses of data from DeStress, a longitudinal study of 251 spousal dementia caregivers in Ireland. We used multivariate logistic and linear regression analyses to examine whether lack of choice (a dichotomous item) and/or the perceived degree of choice (a 9-point scale) at baseline predicted caregiver health (number of chronic health conditions; self-reported health) and wellbeing (e.g., burden, anxiety, depression, stress, positive aspects of caregiving) and care status (continued care at home or placement in long-term care) at follow-up. Results The vast majority of caregivers (82%) reported that they had no choice in taking up the caregiving role. Nevertheless, nearly three-quarters (74%) responded above the midpoint on the rating scale (Mean = 6.82, SD = 3.22; Median = 9; Mode = 9), indicating they provided care voluntarily. Caregivers who reported a greater degree of choice were more likely to still be providing care at home at follow-up and to identify benefits from providing care. Neither choice nor degree of choice predicted any other caregiver outcomes. Conclusion For the vast majority of spousal dementia caregivers, taking up the caregiving role is not perceived as a choice; yet, most report performing this role voluntarily. Thus, facilitating greater choice may not necessarily diminish the key contribution family caregivers make to the care system. Although we found no evidence that caregiver choice predicted more positive caregiver health and wellbeing, the perception of choice is important in and of itself, and may benefit caregivers by facilitating the identification of positive aspects of care and be a factor in delaying care-recipient placement in long-term care. Future research should be especially mindful of how caregiver choice is assessed and how this may affect the resulting prevalence of choice.